Perception of speech rhythm in second language: the case of rhythmically similar L1 and L2 - Ordin, Mikhail; Polyanskaya, Leona (Frontiers in Psychology, 2015)
We investigated the perception of developmental changes in timing patterns that happen in the course of second language (L2) acquisition, provided that the native and the target languages of the learner are rhythmically similar (German and English). It was found that speech rhythm in L2 English produced by German learners becomes increasingly stress-timed as acquisition progresses. This development is captured by the tempo-normalized rhythm measures of durational variability. Advanced learners also deliver speech at a faster rate. However, when native speakers have to classify the timing patterns characteristic of L2 English of German learners at different proficiency levels, they attend to speech rate cues and ignore the differences in speech rhythm.